Bacteria do it better! Proteomics suggests the molecular basis for improved digestibility of sourdough products. (15th October 2021) - Reale, Anna; Di Stasio, Luigia; Di Renzo, Tiziana; De Caro, Salvatore; Ferranti, Pasquale; Picariello, Gianluca; Addeo, Francesco; Mamone, Gianfranco
Graphical abstract: Highlights: The peptide profiles of sourdough vary among different fermenting lactobacilli. β-amylase, triticin and serpin are primary proteolytic targets in sourdough. Proteolysis in sourdough moderately affects the gluten structure. Celiac disease immunotoxic peptides are resistant to proteolysis. Proteolysis of β-amylase could in part explain the decrease of fermentable sugars. Abstract: The aim of this study was to evaluate the dynamics of proteolysis during dough fermentation started with different lactic acid bacteria species, through the identification of intermediate and small-sized peptides generated during fermentation. Single-strain cultures of Levilactobacillus brevis, Fructilactobacillus sanfranciscensis, Companilactobacillus alimentarius, and Leuconostoc pseudomesenteroides were assayed as sourdough starters. Assays were carried out at lab-scale for 48 h of fermentation, using both unstarted and yeast-leavened dough as controls. Physicochemical and microbiological analyses were combined with peptidomic and proteomic profiling, identifying several hundreds of peptides mainly released from the water-soluble wheat proteins, including β-amylase, triticin, and serpins. Both α- and γ-gliadins were hydrolyzed, though only at the N -terminal domain, while the central protein region – encrypting celiac disease epitopes– remained unaffected. The bacterial-mediated consumption of sugars and the concomitant hydrolysis of starch degrading β-amylase could underlie improved digestibility and several nutritionally beneficial effects of sourdough baked products.